2013
DOI: 10.1108/20468251311323388
|View full text |Cite
|
Sign up to set email alerts
|

Professional learning of teachers through a lesson study process in England

Abstract: PurposeThis paper aims to discuss findings from a development and research project using the lesson study (LS) method in England, which had the overall aim of improving learning opportunities for pupils identified as having moderate learning difficulties (MLD). MLD is one of the most prevalent areas of special educational needs in the UK and the project is the first UK attempt to use LS with pupils with identified learning difficulties. The contexts, mechanisms (processes) and outcomes of the lesson studies ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…The remainder used their professional/craft knowledge only and/or some more general research knowledge. Interviews with teachers who only used professional/craft knowledge in their LSs, suggests that they found this knowledge adequate for their LS use (Ylonen & Norwich, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The remainder used their professional/craft knowledge only and/or some more general research knowledge. Interviews with teachers who only used professional/craft knowledge in their LSs, suggests that they found this knowledge adequate for their LS use (Ylonen & Norwich, ).…”
Section: Discussionmentioning
confidence: 99%
“…Pedagogy adopted : The kinds of pedagogy adopted in the research lessons were identified from analysis of the planning of the research lessons in terms of a scheme (see Table for details), which arose from a fuller analysis of pedagogic approaches used in phase 1 LSs (see Ylonen & Norwich, ).…”
Section: Research Methods and Analysismentioning
confidence: 97%
See 2 more Smart Citations
“…It is done to ensure mutual respect, and it established between the participants, especially in the evaluations, which are used to solve learning difficulties found in the classroom. The LS activity has been proven to improve teachers' professionalism (Ylonen & Norwich, 2013). The results of the preliminary observation showed that teachers mostly dominated the learning process.…”
Section: Introductionmentioning
confidence: 99%